(untitled) (Shaheed Smriti Journal, 2024)
Fieldwork was conducted from July to August 2024 to assess the impact and management of invasive alien plant species (IAPS) in the study area. Using quadrat sampling methods, the presence of 16 invasive alien plant species was recorded. Among them, Chromolaena odorata was found to be the most dominant species in the study area. The study revealed that areas infested with these invasive species lacked native plant diversity, as IAPS inhibit the growth of other herbs, shrubs, and trees by releasing allelopathic chemicals. This leads to significant biodiversity loss, depletion of natural resources, decreased soil fertility, and a reduction in the abundance of valuable medicinal and aromatic plants. The findings underscore the urgent need for effective management strategies to control the spread of these invasive species and mitigate their detrimental effects on ecosystems and biodiversity.